ABOUT HEILONGJIANG INTERNATIONAL UNIVERSITY - Heilongjiang International University (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Heilongjiang International University(HIU) was first established in 1993 as Harbin Star Foreign Language College, the first institute in Heilongjiang to develop Sino-foreign co-operation in education. Since April 2011, it has been known as Heilongjiang International University, the leading private university in the province of Heilongjiang, which is a university passionate about languages and international studies. HIU has 10 faculties and schools and 30 bachelor degree programmes, covering the filed of foreign languages, international business, accounting and finance, hospitality management, art and design and computing science etc. There are 10180 full-time students and over 600 teachers at HIU. With celebrating 27 years of teaching excellence, we have taught over 20,000 students inspired 5,000 students to study abroad. The latest student’s satisfaction rates were 90%, well above the national average, and our employable rate was a 93%. We are proud to be ranked 26th and a five-star university in the national private universities table. HIU is a friendly and welcoming university with a diverse mix of nationalities from all over the world. We have a strong emphasis on delivering education with an international perspective. We have much to offer our international students with an excellent choice of courses available for students in a variety of languages and flexible durations. In the last two years, over 1000 students have gone abroad to study or work in internships with one of HIU’s 104 partners in 32 countries. HIU is a recognized language testing centre for a number of foreign language examinations such as Cambridge English MSE, TestDaf, DELE, CELI, Russian language test etc. We are also a proud of member of international alliances and networks, such as Network of International Business Schools, Association of Asian Universities etc. HIU also has collaboration with University Quisqueya in Haiti to co-build the Confucius classrooms ,which supports with Chinese language and culture teaching.